2006
DOI: 10.1007/s11273-006-9000-z
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of the groundwater in a riverine-type mangrove forest

Abstract: The behavior of groundwater and physical properties of bottom sediment in a riverine-type mangrove forest which is composed of a tidal creek and fringing mangrove swamps were investigated through field observations at Iriomote Island, Japan. After the tidal water ebbed from the swamp surface to the creek, groundwater levels at swamp sites near the creek fell by up to 15 cm by the next flood tide, although the fall was negligible at sites far from the creek and at the open coast outside the mangrove forest. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 11 publications
1
21
0
Order By: Relevance
“…It has been hypothesized that this tidal variation is driven by the input of groundwater enriched in DIC and DOC during the ebb tide (Dittmar and Lara 2001; Bouillon et al 2007b), with connectivity between groundwater and surface water enhanced in mangroves because of the mosaic of macrofauna burrows and organic-rich sediment layers (Ridd 1996;Mazda and Ikeda 2006). We build on these studies by using 222 Rn to quantitatively demonstrate the groundwater input.…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that this tidal variation is driven by the input of groundwater enriched in DIC and DOC during the ebb tide (Dittmar and Lara 2001; Bouillon et al 2007b), with connectivity between groundwater and surface water enhanced in mangroves because of the mosaic of macrofauna burrows and organic-rich sediment layers (Ridd 1996;Mazda and Ikeda 2006). We build on these studies by using 222 Rn to quantitatively demonstrate the groundwater input.…”
Section: Discussionmentioning
confidence: 99%
“…The data encompass oxygen measurements taken at all seven forests Ikeda 2006). Seepage of groundwater through the forest floor is controlled by a number of physical forces (Mazda et al 1990;Susilo et al 2005;Mazda and Ikeda 2006) that result in interstitial water oozing out through the bottom soil, most clearly seen as water moving through seepage channels between the forest and adjacent creek bank. In this study, we sampled water in drainage channels from all seven sites and found that DIC concentrations in the seepage were equivalent to those measured in the interstitial water (with both greater than overlying DIC water concentrations) showing that mineralized carbon is being drained advectively from these forests.…”
Section: Exposed and Inundated Soil Respirationmentioning
confidence: 99%
“…At higher tidal levels closer to land, a greater volume of the forest floor experiences tidal oscillations and faster lateral transport of drainage than flood waters, due to factors such as tidal asymmetry, number and complexity of burrows and other openings, soil texture, the extent of groundwater (if any), and slope of the forest floor (Ridd 1996;Heron and Ridd 2008). This subsurface flow is complex (Mazda and Ikeda 2006), but how it affects microbial metabolism within the forest floor is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of porewater migration depends on the sediment permeability and the pressure gradient. Crab burrows have been found to dramatically enhance the hydraulic conductivity, and given their abundance in mangrove systems, these could be important mediators for subsurface flow of porewater to tidal creeks (Ridd, 1996;Mazda and Ikeda, 2006).…”
Section: Introductionmentioning
confidence: 99%